Effects of surface functional groups of activated carbon on adsorption of triclosan from aqueous solution. (1st December 2008) - Fang, Sheng Fu; Pendleton, Phillip; Badalyan, Alexander
We report adsorption of triclosan by using activated carbons as a potential method to improve the discharge water purification process. Commercially available activated carbons, P1300, Picazine HP and Hydrodarco C, display different levels of affinity for triclosan from aqueous solution. Surface chemistry of these adsorbents were modified via reduction, oxidation and nitridation, to improve and better understand the adsorption process. The adsorption capacity was greatly influenced by surface group changes, with a decrease in relative affinity on oxidation. Nitridation enhanced the amounts adsorbed over the thermally reduced samples. Surface analysis via X-ray Photoelectron Spectroscopy (XPS) helped us identify the introduced surface functional group changes. Overall, nitridation resulted in an increased basic character of the surface exploiting the Lewis acidic nature of triclosan when it is dissolved in solution. The surface chemistry modified adsorbents suggest that adsorption from solution is a viable methodology for triclosan control during wastewater treatment.